Improving Student Lifestyles through Health Quality Assurance - Nadya; Mabruroh; Naufal (Al-Qalam Institue, 2024)
This paper describes the quality assurance of health in improving the healthy lifestyle of students in Islamic boarding schools, highlighting its impact on students' comfort in learning. The research was conducted at the Nurul Jadid Islamic Boarding School. The research employed a qualitative descriptive method with a case study approach. Data collection techniques included interviews, observation, and documentation. Informants comprised health sector consultants, health division coordinators, and students selected through purposive sampling. Data analysis followed the Milles and Huberman framework, involving data presentation, reduction, and conclusion. The results indicate that the quality of health services at Nurul Jadid is well-assured, evidenced by the numerous health service programs provided by the Health Division. This research is expected to offer contributions and benefits, including (1) an assessment of the extent to which Nurul Jadid Islamic Boarding School has improved student health, (2) evaluation materials for the health service coordinator, and (3) considerations on the importance of enhancing health services for students.